Development of monoclonal antibody‐based sandwich ELISA for detecting major mango allergen Man i1 in processed foods - Tsai, Wen‐Che; Yin, Hsin‐Yi; Chen, Ssu‐Ning; Chang, Hung‐Chi; Wen, Hsiao‐Wei (Journal of food safety, 2021)
Mango (Mangifera indica L.) is a popular tropical fruit but also an allergenic source. In Taiwan, the packaging of any food product that contains mango must display an allergen warning. Therefore, establishing a reliable method for detecting mango residues in food products is important. In this study, a sandwich enzyme‐linked immunosorbent assay (sELISA) was developed to detect the major mango allergen Man i1. First, five batches of polyclonal and monoclonal antibodies against Man i1 were generated and used to identify the optimal antibody pair for sELISA. Using 2G5 mAb as the capture antibody and anti‐rMan i1 pAb as the detection antibody yielded the strongest assay signal. The limit of detection (LOD) and limit of quantification (LOQ) of the developed ELISA are estimated to be 3.9 and 21.2 ng/ml rMan i1, respectively, after optimization. The assay exhibits good specificity to mango and offers good precision and reproducibility since the calculated coefficient of variation (CV) of the intra‐ and inter‐assays were 5.5–11.7% and 7.4–12.4%, respectively. Finally, 23 commercial food products were evaluated using the developed sELISA and the results of this assay closely agreed (95.7%) with those of the Western blot. Thus, the developed sELISA provides a potential method for detecting mango allergens in foods for protecting people with mango allergy from the accidental ingestion of mango.